PENDETEKSIAN TITIK – TITIK JANGKAR UNTUK VERIFIKASI FACE 3D - Dahlan Abdullah; Safwandi Safwandi (TECHSI - Jurnal Teknik Informatika, 2012)
This paper outlines methods to detect key anchor points in 3D face scanner data. These anchor points can be used to estimate the pose and then match the test image to a 3D face model. We present two algorithms for detecting face anchor points in the context of face verification; One for frontal images and one for arbitrary pose. We achieve 99% success in finding anchor points in frontal images and 86% success in scans with large variations in pose and changes in expression. These results demonstrate the challenges in 3D face recognition under arbitrary pose and expression. We are currently working on robust fitting algorithms to localize more precisely the anchor points for arbitrary pose images.